Scrapping ritual: Iron Age metal recycling at the site of Saruq al-Hadid (U.A.E.). (January 2019) - Stepanov, Ivan; Weeks, Lloyd; Franke, Kristina; Rodemann, Thomas; Salvemini, Filomena; Cable, Charlotte; Al Ali, Yaaqoub; Radwan, Mansour Boraik; Zein, Hassan; Grave, Peter
Abstract: This paper presents an integrated approach to the identification of complex re-processing operations of ancient ferrous artefacts from the multi-period site of Saruq al-Hadid, Dubai, United Arab Emirates. Spatial and morphological studies and a range of archaeometric analyses – optical microscopy, X-Ray diffraction, Micro-Raman spectroscopy, neutron tomography – are used to identify various processing markers preserved in these heavily corroded objects and to distinguish two groups of differently processed fragments. The main analytical focus is the investigation of corrosion layers preserving traces of hot oxidation and forging of metallic iron, along with re-heating of previously formed rust layers. The collected evidence suggests that the numerous iron artefacts ritually deposited of at the site in the early Iron Age were subsequently retrieved and re-forged into semi-products as a part of larger scheme of recycling operations, in which Saruq al-Hadid was a first node. Graphical abstract: Highlights: Investigation of ancient corroded iron artefacts from the desert near modern Dubai. We present morphological and microstructural analyses of 90 ferrous objects. Artefacts preserve traces of hot oxidation, forging and re-heating of initial rust. Large-scale re-processing of artefacts was undertaken long after their original ritual deposition.